2021
DOI: 10.1108/ci-02-2021-0033
|View full text |Cite
|
Sign up to set email alerts
|

Building information modeling as a tool for prevention of design defects

Abstract: Purpose In recent decades, professionals in the architecture, engineering and construction industry have come to recognize building information modeling (BIM) as one of the most powerful technologies available to ensure successful project outcomes. The purpose of this paper is to explore the benefits of BIM on design defect prevention during the design phase of building projects. Design/methodology/approach The authors qualitatively analyzed 160 design defect leading indicators (LIs) to identify key themes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Several researchers examined how BIM can be integrated in the project life cycle at the very beginning, Liu et al (2018) suggested that BIM can replace the traditional methods for conducting the preliminary and feasibility studies of the concept stage of the project (Liu et al , 2018). Using BIM and creating a 3D model at this stage, requires expending more efforts and elevating the design levels at a very early stage, which is not the norm in conventional construction project management, where concept designs are usually very basic and contain minimal detailing (Koo and O’Connor, 2021; Liu et al , 2018). However, having the initial BIM model at this stage will also facilitate scheduling, cost management and understanding the scope for all project stakeholders (Alashmori et al , 2020; Nguyen et al , 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Several researchers examined how BIM can be integrated in the project life cycle at the very beginning, Liu et al (2018) suggested that BIM can replace the traditional methods for conducting the preliminary and feasibility studies of the concept stage of the project (Liu et al , 2018). Using BIM and creating a 3D model at this stage, requires expending more efforts and elevating the design levels at a very early stage, which is not the norm in conventional construction project management, where concept designs are usually very basic and contain minimal detailing (Koo and O’Connor, 2021; Liu et al , 2018). However, having the initial BIM model at this stage will also facilitate scheduling, cost management and understanding the scope for all project stakeholders (Alashmori et al , 2020; Nguyen et al , 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Then, key supporting themes for BIM were identified by matching appropriate BIM functions with each theme. This study identified the necessary data, project stakeholders, operations, and applicable BIM functions to prevent specific design defects [7].…”
Section: Related Workmentioning
confidence: 99%
“…This process model can also complement many on-going efforts (e.g., [23,32,39]) that looked into 4D BIM in modular projects. The approach in this research further sheds light on object-based complexities in 4D BIM and more importantly overcomes many of the design inefficiencies [7,40].…”
Section: Lean-integrated 4d Bim In Modular Constructionmentioning
confidence: 99%